1988
DOI: 10.1039/dt9880001957
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of new heteronuclear complexes with bridging carbyne ligands between tungsten and gold. X-Ray crystal structure of [AuW(µ-CC6H4Me-4)(CO)2(bipy)(C6F5)Br]

Abstract: The compound [W(-CR)(CO),(q-C,H,)] ( R = C,H,Me-4) (1) reacts with [Au(C,F,)(tht)] (tht = tetrahydrothiophene) t o give the tungsten-gold complex [AuW(p-CR) (CO),( C, F, ) (q-C,H,)]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1988
1988
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…It has been observed that ligands in Au(I) complexes that deviate from linear geometry cause the energies of the 5d orbitals to rise, which strengthens the backdonation from the Au(I) center to the ligand (CO). 44 It is interesting to note that the structural differences observed between borylene coordination to coinage metals and other transition metal fragments closely reect those reported for analogous alkylidyne chemistry: when coordinated to Au + , alkylidynes also exhibit larger Mm C-R angles and shorter Mm C bonds than bridging alkylidynes with most other metals, where the m CR vector is closer to perpendicular to the M-Au bond 4,[45][46][47][48][49][50] These ndings further demonstrate the unique bonding characteristics of coinage metals.…”
Section: Resultsmentioning
confidence: 52%
“…It has been observed that ligands in Au(I) complexes that deviate from linear geometry cause the energies of the 5d orbitals to rise, which strengthens the backdonation from the Au(I) center to the ligand (CO). 44 It is interesting to note that the structural differences observed between borylene coordination to coinage metals and other transition metal fragments closely reect those reported for analogous alkylidyne chemistry: when coordinated to Au + , alkylidynes also exhibit larger Mm C-R angles and shorter Mm C bonds than bridging alkylidynes with most other metals, where the m CR vector is closer to perpendicular to the M-Au bond 4,[45][46][47][48][49][50] These ndings further demonstrate the unique bonding characteristics of coinage metals.…”
Section: Resultsmentioning
confidence: 52%
“…Table 26 were synthesized via reactions for which the n a t u r e of the p r o d u c t could not be predicted in advance. However, the reagents [Cu(THF)(T)-C 5 Me 5 )] 2 9 0 ' 2 9 2 a n d [Au(SC 4 H 8 )(C 6 F 5 )] 292 ' 302 have been used to introduce C u ( T | -C 5 M e 5 ) a n d Au(C 6 F 5 ) groups, respectively, into n e u t r a l dimeric precursors. V c o ( c m " 1 ) f o r R = P h , 2048 s, 2008 s, 1 9 8 2 s, 1 9 7 …”
Section: Yes No Yes Yes No Yesmentioning
confidence: 99%
“…The π-activation of unsaturated hydrocarbons, such as alkenes, dienes, alkynes, or allenes, via coinage metals is well-established and led to numerous methodologies and applications, especially in organic chemistry and catalysis. Coinage metals are also known to efficiently coordinate to a number of heteroelement-based π-systems, yet practical applications of the latter still remain limited. Despite the interest of metal–carbon triple bonds in organometallic chemistry, the activation of MC motifs via external d-block metal centers is still in its infancy.…”
Section: Introductionmentioning
confidence: 99%